The morphology of the greater palatine canal and the greater palatine foramen in women of the first adulthood period - O.V. Kalmin; A.V. Efremova; L.A. Zyul'kina (Известия высших учебных заведений. Поволжский регион: Медицинские науки, 2021)
Background. The purpose of the research is to study the anatomical features of the greater palatine foramen and the greater palatine canal in women of the first adulthood period. Materials and methods. The object of the study is 132 women of the first adulthood period (from 21 to 35 years). We studied the size characteristics of the greater palatine foramen and its shape; the size characteristics of the greater palatine canal and its shape. Results. It was found that the medio-distal diameter of the greater palatine foramen was 3.02 ± 0.63 mm on the right; 3.04 ± 0.64 mm on the left; the antero-posterior diameter was 4.99 ± 0.72 mm on the right, and 5.09 ± 0.74 mm on the left. The mediodistal diameter of the greater palatine foramen on the left is statistically significantly larger than on the right by 0.7 %; the antero-posterior diameter of the greater palatine foramen on the left is larger than on the right by 2 % (p < 0.01). 11 forms of the greater palatine foramen were identified: oval, elongated in the antero-posterior direction; oval, elongated in the medio-distal direction; rounded; semicircular; teardrop-shaped; ovoid; triangular; crescent-shaped; helical; diamond-shaped; bean-shaped. Mostly, the oval shape of the greater palatine foramen was revealed, elongated in the antero-posterior direction, less often-helical. The length of the greater palatine canal was 31.9 ± 2.7 mm on the right; 30.3 ± 2.9 mm on the left. It was found that the length of the greater palatine canal on the right is statistically significantly greater than on the left by 2.7 % (p < 0.01). Bilateral differences in the diameters of the greater palatine canal in the upper, middle, and lower third were statistically unreliable (p > 0.05). 6 forms of the greater palatine canal were identified: sickle-shaped; wave-shaped; hourglass shape; funnel shape with a bend in the lower third; channel straight and zigzag shape. Mostly, the sickle-shaped form of the greater palatine canal was detected, less often-the funnel-shaped channel with a bend in the lower third. Conclusions. The greater palatine canal and the greater palatine foramen have pronounced variability in size and shape. The greater palatine canal has pronounced bilateral differences in length; the greater palatine foramen has pronounced bilateral differences in medio-distal and antero-posterior diameters.